The Influence of Ag2Te Addition on Thermoelectric Properties of Bismuth Telluride - S. Drzewowska; Tian-Wey Lan; B. Onderka (Archives of Metallurgy and Materials, 2022)
The resistivity, Seebeck coefficient and thermal diffusivity were determined for Bi2Te3 + Ag2Te composite mixtures. Subsequent measurements were carried out in the temperature range from 20 to 270°C, and for compositions from pure Bi2Te3 to xAg2Te = 0.65 selected along the pseudo-binary section of Ag-Bi-Te ternary system. It was found that conductivity vs. temperature dependence shows visible jump between 140 and 150°C in samples with highest Ag2Te content, which is due to monoclinic => cubic Ag2Te phase transformation. Measured Seebeck coefficient is negative for all samples indicating they are n-type semiconductors. Evaluated power factor is of the order 1.52·10–3 and it decreases with increasing Ag2Te content (at. %). Recalculated thermal conductivity is of the order of unity in W/(m K), and is decreasing with Ag2Te addition. Finally, evaluated Figure of Merit is 0.43 at 100°C and decreases with temperature rise.